The Gas-Solid Interface Heats of Adsorption of Simple Molecules on Microporous Carbons and on Graphitized Carbon Blacks, at Low Surface Coverage - Stoeckli, Fritz (My University, 1974)
The heats of adsorption of nitrogen, argon, xenon, pentane, cyclohexane and benzene on a typical microporous carbon have been measured by gas-solid chromatography. An overall comparison of the limiting heats of adsorption on active carbons and on graphitized carbon blacks shows a ratio of 1.6 between them. This is also the value of the ratio of the minima of the adsorption potentials. This result is discussed in terms of simple models for the shape of the micropores. Slot-like pores give a better agreement.